UNIVERSITY ENVIRONMENT AS AN ADAPTATION FACTOR OF INTERNATIONAL STUDENTS IN RUSSIA - Galina V. Grishina (Russian Journal of Education and Psychology, 2024)
Background. Internationalisation of education defines the route of modern universities. They need to solve problems related to attracting international students, maintaining the number of them and providing pedagogical support for their adaptation. Universities have to create effective pedagogical conditions that facilitate the adaptation of international students. The specialists study the factors influencing this process, and one of the factors is the university environment.